Trauma, Temperament, Alexithymia, and Dissociation Among Persons Addicted to Alcohol: Mediation Model of Dependencies - Zdankiewicz-Ścigała, Elżbieta; Ścigała, Dawid K. (Frontiers in Psychology, 2018)
Objective: The attachment theory has been conceptualized as an affect regulation theory, proposing that attachment is associated with the expression and recognition of emotions as well as interpersonal functioning. The purpose of the study was to examine a model, in which a relation was analyzed between childhood trauma, temperament, alexithymia, and dissociation in a group of individuals addicted to alcohol. Method: The total number of 201 persons were examined, comprising 67 women (33.3% of participants) and 134 men (66.7% of participants). The participants aged from 18 to 68 (M = 32.81; SD = 12.12). In order to measure the analyzed variables, the following questionnaires were applied: MAST, SSSV, TAS20, TEC, and CES. Results: A comparative analysis between the group of alcohol addicts and non-addicts showed statistically significant differences related to: the intensity of trauma, temperament, alexithymia, and dissociation. The study of models related to the impact of traumatic experience intensity on the level of alcohol addiction with regard to a mediatory role of alexithymia, dissociation, and temperament showed the existence of several important indirect effects, and the model, which takes into account all three mediators, is statistically significant F(4,196) = 35.1964; p < 0.001. Conclusion: Childhood trauma, as well as alexithymia and dissociation block dealing with stress based on self-reflection and self-control, and contribute to affective disorders and their regulation with alcohol. Limitations: The selection of participants to homogeneous groups with regard to age and gender constituted the most important difficulty and limitation. A perfect age criterion for investigating the interaction between the temperament and the consequences of traumatic development would be early adulthood.